Empathy in Chinese eight-year medical program students: differences by school year, educational stage, and future career preference - Dongju Li; Huiming Xu; Mingyi Kang; Shulan Ma (BMC Medical Education, 2018)
Abstract Backgroud To examine the psychometric properties of a Chinese translation of the Jefferson Scale of Empathy (Student-version, JSE-S), and to study differences in empathy scores among eight-year undergraduate medical students across gender, year of study, and future career preference. Methods The JSE-S was administered to 442 participants from December 2016 to July 2017, who were all first- to seventh-year students on an eight-year medical education course at Fudan University. Factor analysis was used to examine the underlying components of the Chinese version of the JSE-S. The data analyses comprised a t-test and analyses of variance. Results Factor analysis confirmed four components: perspective taking, compassionate care, ability to stand in patient’s shoes, and difficulties in adopting patient’s perspective. The lowest empathy score was found in the seventh-year students (99.5), while a decline was found across school years. Students in clinical training (sixth/seventh year) had lower empathy than students in premedical study (first/second year), basic medicine (third/fourth year), and clinical medicine (fifth year). Statistically significant differences in empathy mean scores were found in respect of future career preference but not gender. Students who preferred not to become doctors had lower empathy than students who preferred to become doctors, who were undecided, and who did not specify. Conclusions The findings support the construct validity and reliability of the Chinese version of the JSE-S for medical students. The study also revealed the features of empathy in eight-year program students, and provided a reliable reference to design interventions to cultivate empathy among Chinese medical students.